Using the Internet registries to construct а structural model for locality estimation in the overlay networks - Poryev, G.V. (Реєстрація, зберігання і обробка даних, 2011)
The structure of the database files of the regional Internet registries is analyzed. With the help of proposed method for the locality class estimation is calculated the topological affinity for arbitrary address pairs without using any service traffic. The proposed locality class metric can be used as a distance substitute instead of the traditional trace and ping metrics to construct optimal overlay structure of the distributed and peer-to-peer networks.